Transient neurological deterioration due to watershed shift after STA-MCA bypass surgery in acute atherosclerotic occlusion. (March 2020) - Kim, Seung Hwan; Lee, Hyungon; Kim, Hye-Jin; Choi, Byeong-Sam; Jin, Sung-Chul
Highlights: STA-MCA bypass surgery can be a last treatment option for atherosclerotic occlusion. Watershed zone shift has been reported after bypass surgery for Moyamoya disease. We hypothesized that this conception is also applicable for acute atherosclerotic occlusion. Cerebral infarctions near the newly formed border zone developed after bypass surgery. Abstract: Superficial temporal artery (STA)-middle cerebral artery (MCA) bypass surgery is considered not the primary but the last treatment option for acute atherosclerotic occlusions refractory to medical treatment. We retrospectively evaluated patients who underwent STA-MCA bypass surgery for acute atherosclerotic occlusion intractable to other treatments. From June 2010 to May 2014, 10 patients underwent STA-MCA bypass surgery for acute atherosclerotic occlusion at our hospital. The sites of occlusion were the internal carotid artery (n = 5) and the proximal MCA (n = 5). All 10 patients showed good patency in the anastomosis after bypass surgery, and postoperative cerebral angiography showed a newly formed border zone between the existing collateral blood flow and bypass graft blood flow. Transient neurological deterioration (TND) developed in 4 patients after STA-MCA bypass surgery (40%). All 4 patients showed worsened hemiparesis or aphasia 2–3 days after bypass surgery and improvement in neurological deficits within 1 week after bypass surgery. Diffusion MRI in patients with TND showed new cerebral infarctions near the newly formed border zone. In our series of bypass surgeries for acute atherosclerotic occlusion, postoperative changes in hemodynamic status, also called watershed zone shift, may be one of the causes of new cerebral infarctions near the newly formed border zone.